1993
DOI: 10.1002/pd.1970130611
|View full text |Cite
|
Sign up to set email alerts
|

Disappearing lung echogenicity in fetal bronchopulmonary malformations: A reassuring sign?

Abstract: Congenital bronchopulmonary malformations detectable on prenatal ultrasound include cystic adenomatoid malformation (CAM), lobar sequestration, and upper airway atresia. We describe three fetuses with prenatally detected intrathoracic lesions in which the associated pulmonary hyperechogenicity disappeared before delivery. In the first case of pulmonary sequestration, the infant was asymptomatic after birth. However, in a case of CAM and another with laryngeal atresia, respiratory distress developed after deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Although there may be some slight variation in the definition of hydrops at a given institution, the precise reasons for the more positive outcomes obtained in our study remain unclear. Moreover, there have been at least a dozen reported cases documenting resolution of fetal CCAMs with fluid noted in the pleural and/or abdominal cavities [2,[19][20][21][22][23][24][25]. Anecdotally, the administration of antenatal steroid therapy may also facilitate resolution of these lesions in the setting of hydrops [26].…”
Section: Discussionmentioning
confidence: 97%
“…Although there may be some slight variation in the definition of hydrops at a given institution, the precise reasons for the more positive outcomes obtained in our study remain unclear. Moreover, there have been at least a dozen reported cases documenting resolution of fetal CCAMs with fluid noted in the pleural and/or abdominal cavities [2,[19][20][21][22][23][24][25]. Anecdotally, the administration of antenatal steroid therapy may also facilitate resolution of these lesions in the setting of hydrops [26].…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in the majority of these fetuses the sonographic appearance was that of a solid echogenic mass, which had been thought to carry a poor prognosis.1.S,6,8 Although the fetuses in our study who had resolution of their chest masses did well, Meager and colleagues report several cases in which lung echogenicity improved with persistent underlying pathologic processes and respiratory distress at birth. 12 Meizner and Rosenak report a case of an intrathoracic mass thought to be a pulmonary sequestration, which resolved in utero. The newborn infant had significant respiratory distress and was diagnosed has having a large mucous plug.…”
Section: Discussionmentioning
confidence: 99%
“…, Meagher et al (1993) and Kalache et al (1997) suggested that the diagnosis of laryngeal abnormalities in the fetus is difficult even when prenatal ultrasonography shows increased echogenicity of the lungs and fetal ascites. The prenatal ultrasonography should be examined by a clinical geneticist and post-mortem examination should be performed by a fetal pathologist.…”
Section: Introductionmentioning
confidence: 98%